2001
DOI: 10.1074/jbc.m103391200
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Hydrodynamic Properties of Human Tropoelastin

Abstract: Tropoelastin is the soluble precursor of elastin that bestows tissue elasticity in vertebrates. Tropoelastin is soluble at 20°C in phosphate-buffered saline, pH 7.4, but at 37°C equilibrium is established between soluble protein and insoluble coacervate. Sedimentation equilibrium studies performed before (20°C) and after (37°C) coacervation showed that the soluble component was strictly monomeric. Sedimentation velocity experiments revealed that at both temperatures soluble tropoelastin exists as two independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Supplemental Figure S2 shows the hydrodynamic radius (Rh) vs. intensity distribution of all silk-tropoelastin samples in 0.1-wt% solution (SE0, SE10, SE25, SE50, SE75, SE90, and SE100). Notably, scattered light at a hydrodynamic radius (Rh) of around 6 nm with a predicted molecular weight of 59±12 kDa for sample SE0 is due to pure tropoelastin monomers in solution, as previously reported 35, 36 . In contrast, pure silk (SE100) showed strong intensity of scattered light at Rh of 57.1±9.1 nm and a predicted molecular weight of 427±84 kDa, indicating that silk monomers and some small silk aggregates were formed in solution 12, 22 .…”
Section: Resultssupporting
confidence: 79%
“…Supplemental Figure S2 shows the hydrodynamic radius (Rh) vs. intensity distribution of all silk-tropoelastin samples in 0.1-wt% solution (SE0, SE10, SE25, SE50, SE75, SE90, and SE100). Notably, scattered light at a hydrodynamic radius (Rh) of around 6 nm with a predicted molecular weight of 59±12 kDa for sample SE0 is due to pure tropoelastin monomers in solution, as previously reported 35, 36 . In contrast, pure silk (SE100) showed strong intensity of scattered light at Rh of 57.1±9.1 nm and a predicted molecular weight of 427±84 kDa, indicating that silk monomers and some small silk aggregates were formed in solution 12, 22 .…”
Section: Resultssupporting
confidence: 79%
“…Results from previous experiments proposed a nucleationcondensation model for coacervation of full-length tropoelastin SHEL⌬26A at 37°C (21). This model, together with the putative dominant role for domains 18, 20, 24, and 26 during coacervation, suggested that even though SHEL17-27 did not coacervate at 37°C, it may have been able to self-polymerize as part of the nucleation phase prior to coacervation.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated a greater capacity for intermolecular interactions by SHEL17-27 compared with individual hydrophobic domains. It is possible that at a sufficiently high concentration, SHEL17-27 could form a high molecular weight oligomer that may be representative of the nucleating species for the nucleation-condensation model described for tropoelastin (21). These oligomers, however, may not necessarily be dimers and do not account for the coacervation of full-length tropoelastin under physiologically relevant conditions at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Elastin resilience is afforded by the formation of insoluble fibers, the first step of which involves the selfalignment of elastin monomers, tropoelastin, in a temperature-induced transition known as coacervation, through the association of hydrophobic domains (1,2). Although highly (Ͼ75%) non-polar in character, tropoelastin remains predominantly monomeric and structurally disordered in solution (3)(4)(5) and critically, retains substantial backbone hydration and flexibility even when assembled (6) and cross-linked into mature, polymeric elastic arrays (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%